g factors as a probe of correlated changes of the nuclear deformation and pair field in ground-state rotational bands - Bengtsson, Ragnar; Åberg, Sven (Physics Letters B, 1986)
Theoretical calculations show that both the deformation and the pair field change considerably with increasing spin in the ground-state band of transitional rare-earth nuclei with neutron number close to 90. As a consequence of these changes the g factor is expected to show a significant spin dependence in the ground band of certain transitional nuclei. It is suggested that g-factor measurements may give important information about how changes in the neutron and proton pair fields are correlated to changes in the nuclear deformation.